Trends in Short Birth Length and Stunting Incidence in Blora, 2019-2023 - Kurniatri, Maniek indah; Widyaningsih, Vitri; Sukamto, Ika Sumiyarsi (Global Health Science Group, 2024)
Babies born with short birth lengths tend to face challenges in achieving optimal growth, leading to stunting issues during childhood and suboptimal adult height. Monitoring trends and prevalence of babies born with short birth lengths and stunting is essential to understand community nutrition problems and evaluate the success of nutrition interventions over time. Objective: This study aims to identify trends and prevalence of babies born with short birth length and stunting incidence. Methods: This descriptive study utilizes secondary data from the Blora District Health Office for 2019-2023. The data includes information on the prevalence of short birth length and stunting from 26 community health centers in the Blora District. Results: The prevalence of short birth length from 2019 to 2023 significantly decreased from 10.48% in 2019 to 2.15% in 2023. Over the past five years, there has been a reduction of 8.33%, or 1.66% per year. Meanwhile, the prevalence of stunting was 10.48% in 2019, increased to 14.96% in 2020, and then decreased to 2.15% by 2023. Conclusion: The prevalence of babies born with short birth length has decreased by 8.33% over the past five years. The peak prevalence of stunting in 2020 indicates that the nutrition interventions implemented by the Blora District Government have successfully reduced nutrition problems among newborns.